Engineering morphologies of cobalt pyrophosphates nanostructures toward greatly enhanced electrocatalytic performance of oxygen evolution reaction - Du, Hongfang (2020)
Herein, a surfactant- and additive-free strategy is developed for morphology-controllable synthesis of cobalt pyrophosphate (CoPPi) nanostructures by tuning the concentration and ratio of the precursor solutions of Na4 P2 O7 and Co(CH3 COO)2 . A series of CoPPi nanostructures including nanowires, nanobelts, nanoleaves, and nanorhombuses are prepared and exhibit very promising electrocatalytic properties toward the oxygen evolution reaction (OER). Acting as both reactant and pseudo-surfactant, the existence of excess Na4 P2 O7 is essential to synthesize CoPPi nanostructures for unique morphologies. Among all CoPPi nanostructures, the CoPPi nanowires catalyst renders the best catalytic performance for OER in alkaline media, achieving a low Tafel slope of 54.1 mV dec-1 , a small overpotential of 359 mV at 10 mA cm-2 , and superior stability. The electrocatalytic activities of CoPPi nanowires outperform the most reported non-noble metal based catalysts, even better than the benchmark Ir/C (20%) catalyst. The reported synthesis of CoPPi gives guidance for morphology control of transition metal pyrophosphate based nanostructures for a high-performance inexpensive material to replace the noble metal-based OER catalysts.